Comparison and Efficacy of LigaSure and Rubber Band Ligature in Closing the Inflamed Cecal Stump in a Rat Model of Acute Appendicitis. (28th January 2015) - Yeh, Chun-Chieh; Jan, Chia-Ing; Yang, Horng-Ren; Huang, Po-Han; Jeng, Long-Bin; Su, Wen-Pang; Chen, Hui-Chen
Abstract : Safety of either LigaSure or rubber band in closing inflamed appendiceal stump in acute appendicitis has been less investigated. In this study, cecal ligation followed by resecting inflamed cecum was performed to mimic appendectomy in a rat model of acute appendicitis. Rats were sacrificed immediately (Group A) and 7 days (Group B) after cecal resection, respectively. The cecal stumps were closed by silk ligature (S), 5 mm LigaSure (L), or rubber band (R). Seven days after cecal resection, the LigaSure (BL) and silk subgroups (BS) had significantly less intra-abdominal adhesion and better laparotomy wound healing than rubber band subgroup (BR). The initial bursting pressure at cecal stump was comparable among the three methods; along with tissue healing process, both BL and BS provided a higher bursting pressure than BR 7 days after appendectomy. BL subgroup had more abundant hydroxyproline deposition than BS and BR subgroup. Furthermore, serum TNF- α in BR group kept persistently increasing along with time after cecal resection. Thus, the finding that LigaSure but not rubber band is safe in sealing off the inflamed cecal stump in rat model of acute appendicitis suggests the possibility of applying LigaSure for appendectomy via single port procedure or natural orifice transluminal endoscopic surgery (NOTES).